Problematizing lexico-grammatical equivalence in Arabic-English translation - Al-Kenani, Tawffeek Abdou Saeed Mohammed (H. : ĐHQGHN, 2019)
This study deals with the concept of grammatical equivalence in Arabic-English translation. It investigates the problems that encounter student translators (STs) while translating grammatical constructions from Arabic into English. It is based on a parallel corpus of the translations of fve groups of STs at the Department of English, Faculty of Arts, Taiz University, Yemen. The STs are doing their fnal year and by the time of the administration of the tasks, they had already studied 4 translation courses. The study concluded that the structural and morphological differences between Arabic and English have created various problems for the STs. Following Systemic Functional Grammar (SFG), the grammatical problems at the ideational, interpersonal, textual and logico-semantic metafunctions were identifed. The study concluded that the STs encountered various problems in terms of transitivity, modality, thematic structures, logical dependency and logico-semantic relations between the clauses. Those problems have not only affected the stylistic and grammatical aspects of the target texts, but they have sometimes yielded a meaning different from the one intended by the author(s).